Multigenerational Effects on Children's Cognitive and Socioemotional Outcomes: A Within-Child Investigation - Tanskanen A.; Danielsbacka M. (Blackwell Publishing Inc., 2022)
Associations between grandparental investment and child outcomes were investigated using three waves of a longitudinal British Millennium Cohort Study that included children between the ages of 9 months and 5 years (n = 24,614 person-observations from 13,744 children). Grandparental investment was measured by parent–grandparent contact frequency and grandparental financial support. Child cognitive development was measured using the British Ability Scale and socioemotional outcomes using the Strength and Difficulties Questionnaire. Grandparental investment was associated with improved cognitive and socioemotional outcomes among children. However, these associations occurred because of between-person effects and did not exist in within-person analyses that compared the same children over time. The results are discussed in terms of their contribution to multigenerational relationships research.